2021
DOI: 10.1007/s10750-021-04597-8
|View full text |Cite
|
Sign up to set email alerts
|

Insect body size changes under future warming projections: a case study of Chironomidae (Insecta: Diptera)

Abstract: Chironomids are a useful group for investigating body size responses to warming due to their high local abundance and sensitivity to environmental change. We collected specimens of six species of chironomids every 2 weeks over a 2-year period (2017–2018) from mesocosm experiments using five ponds at ambient temperature and five ponds at 4°C higher than ambient temperature. We investigated (1) wing length responses to temperature within species and between sexes using a regression analysis, (2) interspecific bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…Several models have been proposed to explain potential clines of insect body size, including cell size of insects becoming smaller in warmer climates [2], temperature control of the duration of larval instars that triggers molting [2], and limited availability of oxygen in warmer climates [22]. Insects with aquatic larval stages (i.e., merolimnic insects) may be affected in their development in different ways than terrestrial insects [2,23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several models have been proposed to explain potential clines of insect body size, including cell size of insects becoming smaller in warmer climates [2], temperature control of the duration of larval instars that triggers molting [2], and limited availability of oxygen in warmer climates [22]. Insects with aquatic larval stages (i.e., merolimnic insects) may be affected in their development in different ways than terrestrial insects [2,23].…”
Section: Introductionmentioning
confidence: 99%
“…The current acceleration of global climate warming means that understanding the impact of temperature on growth of merolimnic insects is increasingly important [24,25]. Recent research has shown that adult merolimnic insects, affected by elevated temperatures during development, grow to be smaller adults with shorter wings [23,24]. A widespread shift to smaller body sizes can negatively influence the dispersal ability of insects and may be one of several factors causing major changes in merolimnic insect populations [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature is one of the most important environmental factors affecting many aspects of the life cycles of insects [14]. Thermoregulation is critical for ectotherms as it allows them to maintain their body temperature close to an optimum for ecological performance, endotherms able to regulate their own body temperature, whereas ectotherms depend on the ambient temperature, so they depend on their behavior, physiology, morphology, etc., to regulate the body's heat emissions or absorb heat from the outside environment to improve their body temperatures [15][16][17][18][19][20]. The fluctuations are larger than extreme high and low temperatures and can affect insect activities [21,22].…”
Section: Introductionmentioning
confidence: 99%